Self-Help Group-Based Stunting Management (Study on the Volunteer Group for the Acceleration of Stunting Prevention in Batu, Indonesia) - Lendriyono, Fauzik; Pratama, Erwin; Fariziah, Tsaniah (Universitas Muhammadiyah Tangerang, 2023)
In several official reports published in 2019, it is reported that there will be a high number of stunting cases in Batu, East Java, Indonesia. This study aims to describes the volunteer model for accelerated stunting prevention, the self help group by Alfred Hyman Katz. The qualitative approach chosen in this study which are very necessary to reveal all aspects of Volunteers for the Acceleration of Stunting Prevention. Semi-structured interviews and observations through direct involvement in the activities of the five key actors. Data analysis was carried out by grouping interview data with research participants and interpreting the results of observations based on their sub-dimensions and then simplifying sentence quotations. The result reveal that SHG has simple organization and all resources are obtained from members' self-help or network assistance. The communication model is more flexible and informal. SHGconducts social-health advocacy and community empowerment and has a very wide network. This study can be an alternative solution in preventing stunting in other areas with the self help group model. Dalam beberapa laporan resmi yang diterbitkan pada tahun 2019, dilaporkan bahwa akan terdapat tingginya angka kasus stunting di Batu, Jawa Timur, Indonesia. Penelitian ini bertujuan untuk mendeskripsikan model relawan percepatan pencegahan stunting yaitu self help group oleh Alfred Hyman Katz. Pendekatan kualitatif yang dipilih dalam penelitian ini sangat diperlukan untuk mengungkap seluruh aspek Relawan Percepatan Pencegahan Stunting. Wawancara dan observasi semi terstruktur melalui keterlibatan langsung dalam aktivitas lima aktor kunci. Analisis data dilakukan dengan mengelompokkan data wawancara kepada partisipan penelitian dan menginterpretasikan hasil observasi berdasarkan subdimensinya kemudian menyederhanakan kutipan kalimat. Hasilnya menunjukkan bahwa SHG memiliki organisasi yang sederhana dan seluruh sumber daya diperoleh dari swadaya anggota atau bantuan jaringan. Model komunikasinya lebih fleksibel dan informal. SHG melakukan advokasi kesehatan sosial dan pemberdayaan masyarakat serta memiliki jaringan yang sangat luas. Penelitian ini dapat menjadi alternatif solusi pencegahan stunting di daerah lain dengan model self help group.